The dynamic impact of government agricultural expenditure on the agricultural value added in ASEAN-5 countries - Jaroensathapornkul, Jirawat (Asian Journal of Agriculture and Rural Development, 2025)
This study aims to investigate the long-run and short-run impacts of government agricultural expenditure on agricultural value added in ASEAN-5 countries. It employs the Augmented Dickey–Fuller (ADF) unit root test to ensure data stationarity and the Johansen cointegration and Error Correction Model (ECM) to determine the long-run and short-run relationships, respectively. The findings indicate that, after adjusting the data to first or second differences, they are stationary with statistical significance. Based on the Johansen cointegration test, the trace test indicates that government agricultural expenditures have a long-run impact on agricultural value added in ASEAN-5 countries. Additionally, the estimated parameters of the error correction terms suggest that we can correct the disequilibrium in the short-run impacts. The estimation results of the ECM also show that government agricultural expenditure positively affects agricultural value added under different time-lag conditions. The study concludes that the government has played a significant role in enhancing agricultural value added in ASEAN-5 countries up to the present. As government spending is a part of fiscal policy, it is suggested that the government’s agricultural budget be used more efficiently. This will help implement fiscal policy and boost economic growth in the short term.